2014
DOI: 10.3928/01477447-20140124-26
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Humeral Shaft Aseptic Nonunions in Elderly Patients With Opposite Structural Allograft, BMP-7, and Mesenchymal Stem Cells

Abstract: Humeral shaft aseptic nonunions occur in 2% to 10% of patients managed conservatively and 10% to 15% of patients treated surgically. The complex muscular and neurovascular anatomy of the upper limb makes the surgical approach to the fracture site demanding and risky, especially when previous surgeries have been attempted. The clinical consequence of atrophic humeral shaft nonunions is a severe functional limitation that may significantly affect activities of daily living, especially in the elderly. The surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Our literature review revealed only one other study evaluating the clinical effectiveness of BMP-7 in long-bone non-union treatment of elderly adults. Murena et al analyzed the outcome of humeral shaft non-union therapy using BMP-7 in two older adults [31]. They reported BMP-7 to be a safe and effective treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review revealed only one other study evaluating the clinical effectiveness of BMP-7 in long-bone non-union treatment of elderly adults. Murena et al analyzed the outcome of humeral shaft non-union therapy using BMP-7 in two older adults [31]. They reported BMP-7 to be a safe and effective treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of treatment using intramedullary nailing, screw fixation, and plate fixation with or without bone grafts are available; however, the ideal treatment for nonunion of the proximal humerus remains unclear (Allende & Allende, ; King et al, ; Volgas et al, ). Although the recently developed anatomical locking plate has improved the stability of bone fixation for fractures of the proximal humerus (Rose et al, ), additional augmentation to allow acceleration of bone healing may be needed in more complicated cases (Murena, Canton, Vulcano, Surace, & Cherubino, ). Although a vascularized bone graft that has an abundant blood supply and appropriate biological characteristics is considered to be suitable for bone healing, there are few reports of an operative procedure using a locking plate combined with a vascularized bone graft for treating a nonunion of the proximal humerus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this literature research also revealed that most of the clinical findings are based on case reports or case series with small patient populations, characterized by different delivery approaches, anatomical locations, bone pathologies and dosages, which makes it difficult to draw any final conclusion about the real potential of BMPs therapy and the best protocol they can be applied to [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Therefore, further research in this direction is needed.…”
Section: Discussionmentioning
confidence: 99%